Sustained Decrease in Blood Pressure and Reduced Anatomical and Functional Reinnervation of Renal Nerves in Hypertensive Sheep 30 Months After Catheter-Based Renal Denervation. Issue 3 (March 2019) - Singh, Reetu R.; McArdle, Zoe M.; Iudica, Michael; Easton, Lawrence K.; Booth, Lindsea C.; May, Clive N.; Parkington, Helena C.; Lombardo, Paul; Head, Geoff A.; Lambert, Gavin; Moritz, Karen M.; Schlaich, Markus P.; et al.
Abstract : We examined whether renal denervation (RDN) reduced blood pressure (BP), improved glomerular filtration rate, albuminuria, and left ventricular mass in sheep with hypertensive chronic kidney disease (CKD). To examine whether renal nerve function returned in the long term, we examined vascular contraction to nerve stimulation in renal arteries and determined nerve regrowth by assessing renal TH (tyrosine hydroxylase), CGRP (calcitonin gene-related peptide), and norepinephrine levels in kidneys at 30 months after RDN. RDN normalized BP in hypertensive CKD sheep such that BP was similar to that of the normotensive sheep with intact nerves. Glomerular filtration rate decreased by ≈22% in CKD sheep with intact nerves but increased ≈26% in hypertensive CKD-RDN sheep by 30 months. At 30 months, urinary albumin was ≈127% and left ventricular mass was ≈41% greater in CKD sheep with intact nerves than control. However, urinary albumin was ≈60% less and left ventricular mass was ≈40% less in the CKD sheep that underwent RDN compared with intact counterpart. At 30 months in CKD-RDN sheep, neurovascular contraction (≈56%), renal proportion of TH (≈50%), CGRP (≈67%), and norepinephrine content (≈49%) were all less than CKD-intact; all these variables were similar between normotensive-intact and normotensive-RDN groups. RDN caused a sustained reduction in BP and improvements in renal function. Regrowth of renal nerves and return of function were observed in hypertensive CKD-RDN sheep, but levels were only partially restored to levels of intact. These suggest that RDN lowers BP in the long term and is renoprotective and cardioprotective as a result of lesser nerve regrowth in CKD. Abstract : Supplemental Digital Content is available in the text.